Modifikasi Sistem Penggerak Belt Conveyor T92-BC1 - Nur Citra Wahyudianti; Dewin Purnama; Rochsigit Nugroho (Jurnal Mekanik Terapan, 2023)
Belt conveyor is one of the transportation media used to move material in the form of units or bulk spills from one operating system to another. At PT Solusi Bangun Indonesia, one of the belt conveyor is used to alternately transport two types of materials, namely fly ash & bottom ash (FABA) and silica. It causes inconsistent bin filling when the consumption of silica and FABA materials is high at the same time. In addition, problems with the FABA belt conveyor drive system often occur, such as tripping motors, broken chains, and worn sprockets, causing FABA transport to be disrupted. Therefore, it is necessary to modify the belt conveyor drive system so that FABA transport becomes smoother. The methode begins with collecting data in the field or information from supervisors, field studies, carrying out the design process to evaluating the results. The modifications made were by replacing the gearmotor with a power of 11 kW with a rotational output 24 rpm, changing the transmission system from chain-sprocket to a coupling, and increasing the diameter of the head pulley from 478 mm to 560 mm to increase the belt conveyor transport capacity to 125 tons per hour.